Extraction of triterpenoid compounds from Ganoderma Lucidum spore powder through a dual-mode sonication process. (2nd June 2020) - Shen, Shuang-Fei; Zhu, Li-Fang; Wu, Zijing; Wang, Guangkun; Ahmad, Zeeshan; Chang, Ming-Wei
Abstract: Development of drug products from natural sources enable advantageous treatment and therapy options. Bioactive compounds in Ganoderma lucidum spore powder (GLSP) are known for vast antibacterial, antioxidant and anti-cancer properties. Herein, we studied the use of dual-probe ultrasound to extract triterpenoids from GLSP and further investigated the bioactivity of resulting products. FTIR results confirm the presence of key peaks although dual-probe ultrasound varied extraction efficacy. Response surface methodology (RSM) was used to optimize extraction conditions (55:28 for solvent to solid ratio, 10.38 s of ultrasound time and 94% v/v of ethanol concentration). HPLC-Q-TOF-MS confirmed the presence of nine different compounds and in vitro tests confirm good biocompatibility. Extracts are shown to inhibit DPPH radicals, reaching a maximum (61.09 ± 1.38%) at triterpenoid concentrations of 600 µg/mL. Dual-mode assisted extraction provides an enhanced approach for active embedded fiber production on a scale favorable to industry when using optimized process parameters. Furthermore, triterpenoid extracts show antibacterial properties on Staphylococcus aureus and Escherichia coli with potential in antibacterial and anticancer applications.